Performance enhancement of switched affine systems by switched quadratic Lyapunov functions: Applications in DC-DC converters - Yoshimura, Victor L.; Assuncao, Edvaldo [UNESP]; Teixeira, Marcelo C. M. [UNESP]; Mainardi, Edson I. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
This paper proposes design methodologies to include the convergence rate to Switched Affine Systems, intending to reduce the current overshoot in DC-DC converters. The initial step consists in finding Lyapunov matrices for the convergence rate insertion. However, it is observed that the overshoot enhancement leads to the convergence rate deterioration and vice versa. In order to achieve a good trade-off, a new state-dependent switching law is proposed to further enhance the performance, which consists in taking a state-dependent function to change the Lyapunov matrix. In order to show the effectiveness of these techniques, designs and simulations were developed for the buck-boost converter. © 2013 IEEE.
Keywords: DC-DC converters; Linear matrix inequalities; Lyapunov functions; performance evaluation; Switched affine systems